2019
DOI: 10.1074/jbc.ra118.006798
|View full text |Cite
|
Sign up to set email alerts
|

The Ca-loop in thymidylate kinase is critical for growth and contributes to pyrimidine drug sensitivity of Candida albicans

Abstract: from the Ministry of Science and Technology, Taiwan. The authors declare that they have no conflicts of interest with the contents of this article. This article contains Figs. S1 and S2, Tables S1-S3, supporting Methods and Refs. 1-4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…He et al demonstrated that the expression of CAD, a key enzyme in de novo synthesis of pyrimidine, plays a critical role in chemotherapy resistance in STAD [ 52 ]. When the pyrimidine biosynthetic pathway was blocked, the sensitivity of the drug, 5-Fu, to cancer cells, changed [ 53 , 54 ]. We used NMF clustering analysis to identify the genes relevant to pyrimidine metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…He et al demonstrated that the expression of CAD, a key enzyme in de novo synthesis of pyrimidine, plays a critical role in chemotherapy resistance in STAD [ 52 ]. When the pyrimidine biosynthetic pathway was blocked, the sensitivity of the drug, 5-Fu, to cancer cells, changed [ 53 , 54 ]. We used NMF clustering analysis to identify the genes relevant to pyrimidine metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have investigated polyene susceptibility using CRISPR in C. albicans (Min et al, 2018 ; Huang C.-Y. et al, 2019 ) as well as probed the underlying mechanisms of azole susceptibility in C. albicans (Vyas et al, 2015 ; Liu and Myers, 2017a , b ; Chen et al, 2018 ; Shapiro et al, 2018b ; Nishimoto et al, 2019 ), and other Candida species such as C. orthopsilosis (de San Vicente et al, 2019 ; Morio et al, 2019 ), and the highly azole-resistant C. auris (Kim et al, 2019 ; Rybak et al, 2019 , 2020 ). Similar studies, using mutants created with CRISPR-Cas9, have screened for genes involved in echinocandin susceptibility in C. albicans (Lee et al, 2018 ; Lagree et al, 2020 ) and C. glabrata (Hou et al, 2019 ).…”
Section: Applications Of Crispr In Candidamentioning
confidence: 99%
“…CRISPR-mediated deletion of S. cerevisiae CDC8 and CDC43 homologs in C. albicans and C. glabrata , respectively, led to severe fitness defects; in C. albicans , the absence of Cdc8 kinase also sensitized the strain to the polyene amphotericin B and the pyrimidine 5-FUrd, while the lack of GGTase I CDC43 sensitized multiple Candida species to echinocandins (Huang C.-Y. et al, 2019 ; Sun et al, 2020 ). A novel GGTase I inhibitor, L-269289, also demonstrated fungicidal activity against C. glabrata , suggesting that CRISPR-based investigation of essential genes can lead to potential antifungal candidates (Huang C.-Y.…”
Section: Applications Of Crispr In Candidamentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, changes in dynamics may be important to consider in the design of inhibitors that would be useful in cancer chemotherapy. A better understanding of the human enzyme will also assist in the development of agents which are specific for antimalarial 42 and antifungal 43 thymidylate kinases.…”
Section: ■ Conclusionmentioning
confidence: 99%